ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BESARNYA NILAI DANA KOMPENSASI AKIBAT DAMPAK PENAMBANGAN BATUGAMPING - Fitri, Yelli; Haryanto, D. (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2025)
The presence of mining companies in regions with natural resource potential is often regarded as a source of economic hope for local communities. However, not all regions are able to optimize these resources to improve community welfare. In fact, some communities primarily experience the negative impacts of mining activities. Compensation funds serve as a corporate initiative for environmental management, particularly for affected communities. This study aims to analyze the factors influencing the amount of compensation provided. Data were collected through questionnaires distributed to affected residents. Using multiple linear regression analysis, the results reveal that income level and number of family dependents significantly influence the compensation value. The Adjusted R² of 0.551 indicates that 55.1% of the variation in compensation is explained by the independent variables, while the remaining 44.9% is attributed to other factors not examined in this study.